A study on the impact of organizational commitment, work environment, and the moderating effect of job satisfaction towards the security guard retention of Defense Strategist Security Agency Inc. - Aseron, Gabriel Lance (Animo Repository, 2020)
The group is researchers aimed to find and measure the impact of organizational commitment, work environment, and the moderating effect of job satisfaction towards the security guard’s retention of Defense Strategist Security Agency Incorporated. The research team dispersed a survey questionnaire to 92 security guards in which are deployed in SM Inc. locations such as malls and vacant lots; a descriptive and quantitative analysis was conducted to come up with a conclusion. In addition to this, four (4) employees from the top management and two (2) security guards were interviewed. In doing so, the researchers are able to distinguish the factors that are significant in regard to the retention of security guards; the pattern-matching method was used to analyze the interviews. With the use of simple linear regression, it has been found that job satisfaction is a certain moderator for the model of organizational commitment and work environment toward employee retention. Furthermore, this moderating effect of job satisfaction varies in accordance to the different demographic categories of the respondents. With our pattern-matching analysis, the variables had an overall positive effect from both the security guards and the management team. The main concerns of the security guards regarding the low retention rate within the agency include the inadequacy of the current salary rate and personal preferences, which has a conflict with the agency. In addressing these problems, the research team recommends the following: to provide family support; motivate the security guards to pursue a higher education; hold quarterly meetings to celebrate the guards’ performance; provide more monetary rewards and incentives; and lastly to increase the amount of leaves. All recommendations are in line with the goal of increasing organizational commitment, work environment, and job satisfaction all in which will keep the security guard retention high.